Antioxidant Activity of Kombucha Skin Juice Pineapple (Ananas comosus L.Merr) Instant Drink Powder - Rahmah Utami Budiandari; Rima Azara; Lukman Hudi; Allysa Rowihatunnufus Hikmah (Jurnal Teknologi dan Industri Pertanian Indonesia, 2025)
The purpose of this research was to determine the effect of tween 80 concentratin and drying temperature on the antioxidant activity of Kombucha Pineapple skin juice instan drink powder. This study used a Completely Randomized Block Design (CRD) factorial with nine treatments and three replications. First factor was tween 80 concentration (0,5%; 1%; 1,5%) and Second factor was drying temperature (50C, 60C, 70C). Data were statistically analyzed using analysis of variance (ANOVA) and then continued with Honestly Significantly Differential at 5% level. Results of the research showed that the increasing the concentration of tween 80 resulted in increasing antioxidant activity values, while the higher drying temperature resulted in decreasing antioxidant activity. The highest IC 50 value was in the 50C drying treatment with a tween 80 concentration of 1.5% with an antioxidant activity value of 45.40 ppm, the powder drink yield reached 22.59%.